A Diversified Dietary Pattern Is Associated With a Balanced Gut Microbial Composition of Faecalibacterium and Escherichia/Shigella in Patients With Crohn's Disease in Remission. (28th April 2020) - Zhang, Zhengxiao; Taylor, Lorian; Shommu, Nusrat; Ghosh, Subrata; Reimer, Raylene; Panaccione, Remo; Kaur, Sandeep; Hyun, Jae Eun; Cai, Chenxi; Deehan, Edward C; Hotte, Naomi; Madsen, Karen L; et al.
Abstract: Background and Aims: Crohn's disease [CD] is associated with alterations in gut microbial composition and function. The present controlled-intervention study investigated the relationship between patterns of dietary intake and baseline gut microbiota in CD patients in remission and examined the effects of a dietary intervention in patients consuming a non-diversified diet [NDD]. Methods: Forty outpatients with quiescent CD were recruited in Calgary, Alberta, Canada. Based on 3-day food records, patients consuming a lower plant-based and higher red and processed meat-based diet were assigned to the NDD group [ n  = 15] and received a 12-week structured dietary intervention; all other patients were assigned to the diversified diet [DD] control group [ n  = 25] and received conventional management. Faecal microbiota composition, short chain fatty acids [SCFAs] and calprotectin were measured. Results: At baseline the NDD and DD groups had a different faecal microbial beta-diversity [ p  = 0.003, permutational multivariate analysis of variance]. The NDD group had lower Faecalibacterium and higher Escherichia/Shigella relative abundances compared to the DD group [3.3 ± 5.4% vs. 8.5 ± 10.6%; 6.9 ± 12.2% vs. 1.6 ± 4.4%; p  ≤ 0.03, analysis of covariance]. These two genera showed a strong negative correlation [ r s = −0.60, q  = 0.0002]. Faecal butyrate showed a positive correlation with Faecalibacterium [ r s = 0.52, q  = 0.002], and an inhibitory relationship with Escherichia / Shigella abundance [four-parameter sigmoidal model, R = −0.83; r s = −0.44, q  = 0.01], respectively. After the 12 weeks of dietary intervention, no difference in microbial beta-diversity between the two groups was observed [ p  = 0.43]. The NDD group demonstrated an increase in Faecalibacterium [ p  < 0.05, generalized estimated equation model], and resembled the DD group at the end of the intervention [ p  = 0.84, t-test with permutation]. We did not find an association of diet with faecal SCFAs or calprotectin. Conclusions: Dietary patterns are associated with specific gut microbial compositions in CD patients in remission. A diet intervention in patients consuming a NDD modifies gut microbial composition to resemble that seen in patients consuming a DD. These results show that diet is important in shaping the microbial dysbiosis signature in CD towards a balanced community.